Software development of concurrent design for manufacturing process selection of plastic materials - Mohd. Yunus, Mohd. Yusri (2010)
For plastic products, one of the most critical decisions made during the early design stage is the selection of an appropriate manufacturing process. Designers or engineers must concurrently select the suitable plastic materials and its processing method while they develop the part geometry. It is thus meaningful to develop such a system for helping the engineers at preliminary design stages. This project proposes a system of selecting suitable manufacturing processes and materials in concurrent design for manufacturing environment. The prototype system called PROSEP, use Boothroyd-Dewhurst DFM methodology in evaluating and selecting suitable manufacturing process/material. Visual Basic computer programming language is used as a tool for system development. Three major factors are considered; shape attributes of part, material requirements and production characteristics. The working of the prototype system is demonstrated using prismatic and rotational parts case study.